2005
DOI: 10.3844/ajassp.2005.1042.1048
|View full text |Cite
|
Sign up to set email alerts
|

Push-pull Strategy with Trap Crops, Neem and Nuclear Polyhedrosis Virus for Insecticide Resistance Management in Helicoverpa armigera (Hubner) in Cotton

Abstract: Insecticide resistance in Helicoverpa armigera (Hubner) is a major threat to cotton production in India. The virus infection was found to increase the susceptibility of H. armigera to the insecticides. But, use of Nuclear Polyhedrosis Virus (NPV) on a larger scale and on cotton due to leaf alkalinity poses certain practical problems. Hence, studies were carried out to assess the effects of push-pull strategy with trap crops, neem and NPV in cotton for the management of insecticide resistant H. armigera. Field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…) that elicit opposing behaviors (repellency, deterrence, attraction, arrestance, aggregation) and these cues are often used in conjunction with other control methods as part of an integrated pest management strategy (Cook et al 2007). Examples of tools that have been successfully implemented in push-pull systems include biocontrol agents (Duraimurugan and Regupathy 2005), trap crops (Duraimurugan and Regupathy 2005), botanical compounds (Martel et al 2005), mechanical traps (Pike et al 1987, Zhang et al 1997, and toxins (Zhang et al 1997, Duraimurugan andRegupathy 2005). Such strategies can be tailored for the specific target organism with the goal of using behavioral manipulation to maximize the efficacy of each tool.…”
mentioning
confidence: 99%
“…) that elicit opposing behaviors (repellency, deterrence, attraction, arrestance, aggregation) and these cues are often used in conjunction with other control methods as part of an integrated pest management strategy (Cook et al 2007). Examples of tools that have been successfully implemented in push-pull systems include biocontrol agents (Duraimurugan and Regupathy 2005), trap crops (Duraimurugan and Regupathy 2005), botanical compounds (Martel et al 2005), mechanical traps (Pike et al 1987, Zhang et al 1997, and toxins (Zhang et al 1997, Duraimurugan andRegupathy 2005). Such strategies can be tailored for the specific target organism with the goal of using behavioral manipulation to maximize the efficacy of each tool.…”
mentioning
confidence: 99%
“…In addition, push-pull strategies are beginning to be seriously considered as plausible pest control solutions that help to manage insecticide resistance threats. One study assessing the effects of push-pull strategy with trap crops, neem and Nuclear Ployhedrosis Virus (NPV) in Helicoverpa armigera insecticide resistance on cotton, reported that the push-pull strategy was highly effective in reducing the incidence of H. armigera and damage (Duraimurugan & Regupathy 2005).…”
Section: Push-pull Strategy and Insecticidesmentioning
confidence: 99%
“…One should not, however, underestimate the likelihood that these intercrops may also favour infestations of certain pests. This can be an obstacle to the adoption of these practices, even with the use of selective biopesticides on the intercalated crop (Duraimurugan and Regupathy, 2005;Gurr et al, 2004;Mensah and Singleton, 2004).…”
Section: Farmscaping Landscape Farming Habitat Management and Cottomentioning
confidence: 99%